Meningkatkan Hasil Belajar Matematika Melalui Pembelajaran Berdiferensiasi Berbasis Model Problem Posing - Lubis, Wirda Hayatina; Audina, Diki (Jurnal Didaktika Pendidikan Dasar, 2024)
Each student has a unique background, learning style, interests and abilities. The application of differentiated learning based on the problem posing model is believed to accommodate this diversity. This study aims to describe how to apply differentiated learning based on the problem pose model in mathematics learning as well as improving student learning outcomes through the application of differentiated learning based on the problem pose model in the mathematics subject of mixed arithmetic operations in class I of SD Negeri 058374 Sei Limbat. The method used is Classroom Action Research (CAR), which was carried out in two cycles. Each cycle includes the stages of planning, implementation, observation and reflection. Data collection instruments include observation sheets and test sheets. The data from student learning test results were analyzed using the average score formula and percentage of classical learning achievement, observation data on student and teacher activities were analyzed based on the percentage formula for observation results. Based on the research results in each cycle there is an increase. In cycle I, the percentage of classical achievement was 52.94% with an average value of 65.88. In cycle II it increased to 88.24% with an average value of 91.18. From the results of this action research, it can be concluded that through differentiated learning based on the problem posing model, it can improve the learning outcomes of students in class I-B at SD Negeri 058374 Sei Limbat.